Effect of lactosucrose on the evaluation of visual appearance, texture, water mobility, microstructure and inhibition of staling in wheat bread. (31st March 2022) - Zhang, Miaomiao; Xiao, Shensheng; Gong, Aqiong; Liu, Xiaorong; Wu, Yan; Du, Jing; Ding, Wenping; Fu, Yang; Wang, Xuedong
Summary: Starch retrogradation occurred in the process of storage of bread, resulting in a decreased product quality. The aim of this research was to determine the effect of lactosucrose on bread baking and anti‐staling properties. The results showed that the addition of lactosucrose increased the specific volume and slice cell number with a higher air holding capacity. The kinetic equation showed that lactosucrose reduced the rate constant value. Besides, the long‐ and short‐range ordered structure showed that the incorporation of lactosucrose retarded the crystallisation rate, in which the water migration was delayed. This effect was also evident on the microstructure, indicating that lactosucrose could improve the quality of bread and delay the staling of bread, which provided new insights for the baking industry. Abstract : The addition of lactosucrose improves the texture of bread and delays the staling during storage.